Analisis Permintaan Beras Merah di Kota Baubau - Muhamad Iksan; Sitti Aida Adha Taridala; Budiyanto Budiyanto (Universitas Halu Oleo, 2021)
The aim of this study is to analyze the factors that influence the demand for red rice at the household level, and to analyze the degree of sensitivity of the factors that influence the demand for brown rice. The study was conducted in Baubau City from September 2019 to January 2020. The study population was households consuming brown rice. The sample was determined using accidental sampling technique. The number of samples selected was 45 households. Data analysis used multiple non-linear regression. The results showed that the variables of household income, number of household members, housewife education, age and taste all affected the demand for brown rice. Household income, housewife education, age, and taste have a significant effect on the demand for brown rice. The variables that most dominantly affect the demand for brown rice are the number of household members who like brown rice, the degree of sensitivity to changes in household income variables, the education of housewives, age and number of household members who like brown rice are inelastic.Keywords: brown rice; household; demand; Baubau